AURORAL ELECTROJET ノ モンダイテン ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 飯島, 健; イイジマ, タケシ; IIJIMA, Takesi (国立極地研究所, 1972)
P(論文) The essence of the auroral-electrojet is an association with the rapid motion of the aurora. We estimate the three-dimensional current distribution based upon the change of 4278 Å line aurora observed at Syowa Station by HIRASAWA (1971). The auroral luminosity change (the local change plus the change due to the movement) implies the disturbance in the ionosphere electron density distribution over the auroral oval, which is directly associated with the field-aligned current. The ionosphere and magnetosphere electric field is eventually strained and results in the westward ionosphere current asymmetric with respect to the center of the arc (intense in the poleward side and weak in the equatorward side) presumable for the observed ΔH distribution over the auroral oval. departmental bulletin paper